Tracking SDG 7 : The Energy Progress Report 2022 - International Energy Agency (World Bank, Washington, DC, 2022)
This 2022 edition of Tracking SDG 7: The Energy Progress Report assesses achievements in the global quest for universal access to affordable, reliable, sustainable, and modern energy by 2030. At today’s rate of progress, the world is still not on track to achieve the SDG 7 goals by 2030. Advances have been impeded, particularly in the most vulnerable countries and those that were already lagging. From the outset of the pandemic, governments mobilized an unprecedented level of fiscal support to manage the impacts of the pandemic on citizens and the global economy. Appropriations of recovery funds in areas relevant to SDG 7 reached USD 710 billion, but 90 percent of that came in the advanced economies. Emerging markets and developing countries, with their much more limited fiscal leeway, mobilized far less. Increasing clean energy and access investments in these regions requires greater support from international actors.